Hepatitis C Virus-Infected Patients Are ‘Spared’ from the Metabolic Syndrome but Not from Insulin Resistance. A Comparative Study of Nonalcoholic Fatty Liver Disease and Hepatitis C Virus-Related Steatosis - Amedeo Lonardo; Stefano Ballestri; Luigi E Adinolfi; Enrico Violi; Lucia Carulli; Silvia Lombardini; Federica Scaglioni; Matteo Ricchi; Giuseppe Ruggiero; Paola Loria (Canadian Journal of Gastroenterology)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) and chronic hepatitis C feature steatosis and insulin resistance (IR), conditions associated with the metabolic syndrome (MS).